From Khmer treasures to Chinese antiquities: The ongoing plunder and trafficking in South East Asia - Duncan Chappell; Kenneth Polk (Freedom from Fear, 2009)
In June of this year, in a ceremony associated with much pomp and political significance, the Thai Prime Minister Abhisit Vejjajiva handed over to Cambodian officials in Phnom Penh a number of Khmer treasures seized by Thai authorities from smugglers in 1999. The treasures included six massive stone heads of the Hindu God Shiva, dating from the 12th Century Angkorian era (Associated Press, 2009).